Designing and validation of a family-centered emotion regulation program and determining its effect Impulsivity and Family Quality of Life in adolescents with Oppositional Defiant Disorder - Taheri, Marjan; Tajali, Parisa; Shahriari Ahmadi, Mansooreh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: The concern in the area of adolescent mental health and its impact on psychological and behavioral development and functions simultaneously with the increase in the prevalence of mental disorders, particularly oppositional defiant disorder, has increased significantly in adolescents in recent years. The purpose of this study was to designing and validation of a family-centered emotion regulation program and determining its effect on impulsivity and family quality of life in adolescents with Oppositional Defiant Disorder. Methods: The quasi-experimental research design was pretest-posttest and follow-up with the control group. The statistical population of this study included all adolescents 14-18 years old with oppositional defiant disorder in Tehran in 2021-2022. The sample size consisted of 32 Subjects of adolescents (16 in the experimental group and 16 in the control group) from the statistical population were selected by the available sampling method and placed in two groups of control and experimental. For the experimental group, a designed family-centered emotion regulation program was implemented, while the control group did not receive any training. The research instruments included the Adolescent Behavioral Problems Scale (Achenbakh, 1991), Impulsivity Scale (Barrat et al, 2004), and Beach Center Family Quality of Life Scale. Results: The results showed that family-centered emotion regulation intervention had a significant effect on impulsivity and family quality of life in the post-test and follow-up stages (P<0.001). Conclusion: Findings of this study provide useful information about family-centered emotion regulation program and counselors and psychologists can use this intervention to improve impulsivity and family quality of life in adolescents with oppositional defiant disorder